Только с тобой: [роман] / Дженел Тейлор - Тейлор Дженел (Страсть, 2003)
Экземпляры: ф.14 (2003) / Инвентарный номер: 45774 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: Т 30 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44